Acute Mesenteric Ischemia in a 68-Year-Old Woman Presenting with Abdominal Pain: A Case Report - Hutabarat, Rico Alfredo; Raharjo, Suryo Wahyu (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2025)
Acute Mesenteric Ischemia (AMI) is a life-threatening condition caused by a sudden reduction in intestinal blood flow, leading to ischemia and potential bowel necrosis. With a mortality rate of 50–80%, delayed diagnosis due to nonspecific symptoms remains a challenge. The primary causes include arterial embolism, thrombosis, non-occlusive mesenteric ischemia (NOMI), and mesenteric venous thrombosis (MVT). Elderly patients, especially those with cardiovascular disease, are at higher risk. Contrast-enhanced CT angiography (CTA) is the gold standard for diagnosis. A 68-year-old woman presented with a three-day history of abdominal pain and was initially diagnosed with acute abdominal pain due to suspected perforated appendicitis. Imaging showed abdomen without pneumoperitoneum, along with chest radiograph found cardiomegaly and aortic elongation. Exploratory laparotomy was performed on February 15, 2025, revealed multiple mesenteric hematomas indicative of AMI and a hyperemic appendix, leading to an appendectomy. Postoperative care included anticoagulation, antibiotics, and supportive therapy. MSCT confirmed mesenteric ischemia with vascular stenosis and thrombi. On February 20, she developed heparin-induced hematochezia, managed with transfusion and hemostatic therapy. The patient remained stable and was discharged on February 24, 2025. This case illustrates the diagnostic challenges of AMI, often misdiagnosed due to its nonspecific symptoms. Exploratory laparotomy played a crucial role in diagnosis, revealing mesenteric hematomas. Contrast-enhanced MSCT confirmed vascular involvement, highlighting the importance of imaging in AMI detection. Anticoagulation was essential for preventing further thrombosis but required careful monitoring due to the risk of bleeding complications. Early recognition and intervention are vital in managing AMI, especially in elderly patients with cardiovascular risk factors. A multidisciplinary approach, including surgical exploration, advanced imaging, and individualized anticoagulation therapy, is crucial for improving outcomes.